Focus and phrasing in Shingazidja - Patin, Cédric (ZAS Papers in Linguistics, 2008)
It has been established since Kanerva’s work that focus conditions phrasing – directly or indirectly – in several other Bantu languages, e.g. Chimwiini (Kisseberth 2007, Downing 2002, Kisseberth & Abasheikh 2004), Xhosa (Jokweni 1995, Zerbian 2004), Chitumbuka (Downing 2006, 2007), Zulu (Cheng & Downing 2006, Downing 2007), Bemba (Kula 2007), etc.In this paper, I will argue that focus also conditions phrasing in Shingazidja, a Bantu language3 spoken on Grande Comore (or Ngazidja, the largest island of the Comoros).Many works have been dedicated to the tonology of Shingazidja. The bases of the system were firstly identified by Tucker & Bryan (1970) and reanalyzed by Philippson (1988). Later, Cassimjee & Kisseberth (1989, 1992, 1993, 1998) provide a very convincing analysis of the whole system of the language, and my own research (Patin 2007a) shows a great correspondence with their results. However, little attention has been paid by these authors or others (Jouannet 1989, Rey 1990, Philippson 2005) to the phonology-pragmatics interface, especially on the relation between focus and phrasing. This paper thus proposes to explore this question. It will be claimed that focus, beside syntax, has an influence on phrasing in Shingazidja.